PENGUATAN SIKAP TOLERANSI MELALUI EDUKASI PENCEGAHAN BULLYING TERHADAP ANAK BERKEBUTUHAN KHUSUS DI LINGKUNGAN SMP INKLUSI - Amelia Rizky Idhartono; Hidayati, Nurul; Novriyana Santri Yasin; Alsyah Asfarina Subekti (Kanigara, 2025)
Various cases of bullying against children with special needs (ABK) often occur due to a lack of tolerance to children with special needs. Teachers, especially in inclusive schools, are not only required to teach, but also to instill character education, including tolerance among students. A tolerant attitude must first be strengthened and possessed by teachers so that it can be implemented for students without special needs and students with special needs as a whole. Partners in this PkM activity are the Surabaya City Education Office and involve 80 inclusive junior high school teachers. This activity was carried out offline from March 19 to May 18, 2025. In this activity, the lecturer also involved 2 students from the Special Education Department, PGRI Adi Buana University, Surabaya.